The Nitric Oxide System in Peripheral Artery Disease: Connection with Oxidative Stress and Biopterins - Ahmed Ismaeel; Evlampia Papoutsi; Dimitrios Miserlis; Ramon Lavado; Gleb Haynatzki; George P. Casale; William T. Bohannon; Robert S. Smith; Jack Leigh Eidson; Robert Brumberg; Aaron Hayson; Jeffrey S. Kirk; et al. (MDPI AG, 2020)
Peripheral artery disease (PAD) pathophysiology extends beyond hemodynamics to include other operating mechanisms, including endothelial dysfunction. Oxidative stress may be linked to endothelial dysfunction by reducing nitric oxide (NO) bioavailability. We aimed to investigate whether the NO system and its regulators are altered in the setting of PAD and to assess the relationship between NO bioavailability and oxidative stress. Sera from 35 patients with intermittent claudication (IC), 26 patients with critical limb ischemia (CLI), and 35 non-PAD controls were analyzed to determine levels of tetrahydrobiopterin (BH4), dihydrobiopterin (BH2), nitrate/nitrite (nitric oxides, or NOx), arginine, citrulline, asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), and the oxidative stress markers 8-Oxo-2'-deoxyguanosine (8-OHdG), 4-hydroxynonenal (4-HNE), advanced glycation end products (AGEs), and protein carbonyls. NOx was significantly lower in IC and CLI patients compared to controls in association with elevated oxidative stress, with the greatest NOx reductions observed in CLI. Compared with controls, IC and CLI patients had reduced BH4, elevated BH2, and a reduced BH4/BH2 ratio. SDMA, the arginine/SDMA ratio, and the arginine/ADMA ratio were significantly higher in CLI patients. The NO system and its regulators are significantly compromised in PAD. This dysregulation appears to be driven by increased oxidative stress and worsens as the disease progresses from claudication to CLI.